0728 Positive Airway Pressure Adherence In Children with Neuro-Developmental Disorders. (12th April 2019) - Thomas, Caroline; Malow, Beth; Shelton, Althea Robinson
Abstract: Introduction: Obstructive sleep apnea (OSA) contributes to a myriad of behavioral, neuropsychological, and cognitive problems. Children with neurodevelopmental disorders (NDD), already vulnerable to these problems, are even more at risk if they have coexisting OSA. In those children with OSA refractory to surgical treatments, improving positive airway pressure (PAP) adherence (and therefore reducing sleep disturbance) is a novel avenue to mitigate these problems. Despite the increased prevalence of OSA in some NDDs, data are lacking on which children with NDD become adherent to PAP, and which struggle. The purpose of this study was to assess PAP adherence in patients with NDD and identify associations to PAP adherence. Methods: A retrospective chart review was conducted in patients with NDD and residual OSA after adenotonsillectomy (TA), who were treated with PAP therapy. Patients were seen in the Vanderbilt Pediatric Sleep Disorder clinic from January 2012 to January 2017. Patients were grouped as either adherent or non-adherent. Adherence was defined as 70% of the nights with an average usage of ≥ 4 hours per night. Medical comorbidities such as multilevel airway surgery after TA, comorbid sleep disorders, genetic diagnosis, verbal ability, psychiatric disorders and the diagnosis of autism spectrum disorder were also recorded. Associations were assessed using Pearson chi-square test. Results: A total of 54 patients were identified. Forty-two percent were adherent to PAP therapy. Of all medical comorbidities assessed, only the presence of secondary multilevel airway surgery showed a significant association with adherence (p <0.03). Patients who had secondary upper airway surgery after adenotonsillectomy were more likely to be non-adherent to PAP therapy. Conclusion: Our study demonstrates that adherence to PAP therapy in patients with NDD is similar to what has been reported in prior studies (40 to 49%). However, multi-level airway surgery after TA is associated with decreased adherence in this population, in contrast to what has been reported in the neurotypical adult literature. Factors associated with multi-level airway surgery and poor adherence warrant further study. Support (If Any)